Following Tanya’s Lead: The Mirage and Hope of Social Medicine Research - Joshua Franklin (Medicine Anthropology Theory, 2021)
Entrenched structural inequalities raise challenging questions of how socially-oriented research initiatives are likely to improve health for marginalised people. The recent inclusion of transgender women in the National HIV Behavioral Surveillance (NHBS), an ongoing initiative funded by the Centers for Disease Control and Prevention (CDC) to study the HIV epidemic in the US, is designed to redress the exclusion of transgender people from past HIV research and to confront the disproportionate burden of HIV on transgender women through the production of specific knowledge about HIV risk factors in this population. The hope is that such research will ameliorate the burden of HIV among transgender women. Building on a decade-long ethnographic engagement with transgender activists and health practitioners, I delve into tensions between the health research that sustains this horizon of hope and what I call the ‘mirage’ of social medicine research. My interlocutors call out this mirage of scientific optimism in which ‘all the answers are already known’, suggesting that health research oriented towards social justice simply begets more research. Nonetheless, my interlocutors engaged with me, a physician-anthropologist trainee, in order to insist on the ethical necessity of including transgender people in health research even as they exposed the limits of such inclusion and, more broadly, the limits of medicine’s power to redress social injustice. We should follow their lead, embracing neither futility and hopelessness nor the mirage of medical salvation, in order to build collaborative relationships in the service of a more caring social medicine.